Cover Feature: Galvanic Deposition of Pt Nanoparticles on Black TiO2 Nanotubes for Hydrogen Evolving Cathodes (ChemSusChem 22/2021). Issue 22 (28th October 2021) - Touni, Aikaterini; Liu, Xin; Kang, Xiaolan; Carvalho, Patricia A.; Diplas, Spyros; Both, Kevin G.; Sotiropoulos, Sotirios; Chatzitakis, Athanasios
Abstract : The Cover Feature shows the spontaneous galvanic deposition of metallic Pt nanoparticles on the top, but also inner TiO2 nanotube surfaces. High‐aspect‐ratio and heavily reduced TiO2 serves as the sacrificial template during this electroless deposition. A high‐performing and stable hydrogen evolution cathode in acidic media is demonstrated and prepared via minimal engineering and low noble metal loadings. More information can be found in the Full Paper by A. Touni et al .